Pengembangan Multimedia (Audiovisual) Pembelajaran Matematika Pada Materi Bangun Ruang Bagi Siswa Kelas IV SD - Nurul Hikmah (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
This study aims to produce a decent media used in learning mathematics in SD Negeri 005 Samarinda Ulu. This type of research is a development research. The research method adopted in the 4D (Four-D Model) development model consists of four stages: define, design and development. While the dissemination stage (disseminate) is not done.In this study, the respondents were 2 experts, materials experts and media experts, 2 teachers of homeroom teacher, 15 students of small classes and 32 large class students (fourth grade students). Data collection techniques in the form of documentation, questionnaires, interviews and test results learning.Based on the results of research, it is shown that the developed learning media suitable for use in learning mathematics. This can be seen from the result of validation by the lecturer of media experts equal to 85.26% and material experts of 87.37% entered in the criteria is very feasible. This is indicated by the increase in student learning activities expressed in the percentage and data value of learning outcomes of knowledge second class posttest obtained the value of individual and classical completeness of 100% meaning that is complete for small classes while the class of 100% means complete, then the media developed is effective To improve understanding of mathematical concepts for fourth grade elementary school students.